Analisa Kerusakan Mesin Digester Menggunakan Metode Failure Mode Dan Effect Analysis (FMEA) Di PT. Beurata Subur Persada - Yusnazri, Yusnazri; Pribadyo, Pribadyo; Masykur, Masykur (universitas teuku umar, 2025)
Machines that experience damage or disruption during production will cause losses to the company. Efforts to keep the machine from experiencing damage require a good and perfect machine maintenance and care system. PT. Beurata Subur Persada is a company engaged in the palm oil plantation and processing sector. The implementation of the scheduled maintenance system is often hampered, where the Digester machine stops operating due to breakdown. The purpose of the study was to determine the damage to the digester machine. Based on the results of the study using the Failure Modes and Effect Analysis (FMEA) method on the Severity, Occurance and Detection assessment of 4 components that often fail. The results of the study found the levels of Severity, Occurance and Detection of the four components that failed with the highest Severity levels in the Long Arm and Short Arm components of 57.14%. The evaluation of Occurance and Severity has the same value in each component, namely 7 and 3. However, the Detection value has a different value, especially in the gearbox and v belt components. Risk Priority Number from the calculation of Severity, Occurrence and Detection obtained the highest value in the long arm and short arm components of 16.67%, while the lowest Risk Priority Number value was in the gearbox and v-belt components, namely 14.29%.